Long-Term High-Density Extracellular Recordings Enable Studies of Muscle Cell Physiology - Lewandowska, Marta K.; Bogatikov, Evgenii; Hierlemann, Andreas R.; Punga, Anna Rostedt (Frontiers in Physiology, 2018)
Skeletal (voluntary) muscle is the most abundant tissue in the body, thus making it an important biomedical research subject. Studies of neuromuscular transmission, including disorders of ion channels or receptors in autoimmune or genetic neuromuscular disorders, require high-spatial-resolution measurement techniques and an ability to acquire repeated recordings over time in order to track pharmacological interventions. Preclinical techniques for studying diseases of neuromuscular transmission can be enhanced by physiologic ex vivo models of tissue-tissue and cell-cell interactions. Here, we present a method, which allows tracking the development of primary skeletal muscle cells from myoblasts into mature contracting myofibers over more than two months. In contrast to most previous studies, the myofibers did not detach from the surface but instead formed functional networks between the myofibers, whose electrical signals were observed over the entire culturing period. Primary cultures of mouse myoblasts differentiated into contracting myofibers on a chip that contained an array of 26,400 platinum electrodes at a density of 3,265 electrodes per mm2. Our ability to track extracellular action potentials at subcellular resolution enabled study of skeletal muscle development and kinetics, modes of spiking and spatio-temporal relationships between muscles. The developed system in turn enables creation of a novel electrophysiological platform for establishing ex vivo disease models.